Non-crop plant beds can improve arthropod diversity including beneficial insects in chemical-free oil palm agroecosystems - Norhisham, Ahmad R.; Yahya, Muhammad Syafiq; Nur Atikah, Sharifah; Jamian, Syari; Bach, Oliver; McCord, Mona; Howes, John; Azhar, Badrul (Informa Healthcare, 2024)
Conventional oil palm plantations, characterized by monocropping practices, are susceptible to pest infestations due to the lack of diversity in crop composition. This reliance on monoculture often necessitates heavy pesticide use, posing considerable risks to human health, the environment, and biodiversity. In contrast, regenerative agricultural approaches support ecosystem services, such as natural pest control, thereby reducing pesticide dependency and promoting biodiversity while maintaining productivity. The present study examined the composition of arthropod assemblages and understory plant species in chemical-free oil palm plantations, comparing farms with the integration of non-crop plant beds to those without intervention. We established either 10 square plant beds measuring 3 × 3 m or three rectangular beds measuring 9 × 3 m between the planting rows at each experimental plot. Using coloured pan traps and sticky traps, we assessed the relationship between understory plant species richness and arthropod assemblages, including the number of arthropod families, overall abundance, and selected trophic guilds. Our findings reveal that the integration of non-crop plant mixtures significantly enhances the number of arthropod families, as well as the abundance of predatory and phytophagous arthropods. Moreover, we observed that arthropod assemblages, most notably the number of families, overall abundance, abundance of scavengers and predators were significantly and positively correlated with the number of understory vegetation species. The study highlights the potential of establishing non-crop plant bed as a practical approach to enhancing habitat complexity for natural enemies, thereby fostering biodiversity and contribute to the resilience and functioning of agroecosystem within monoculture plantations.